(untitled) (Journal of Universal Science Research, 2025)
In recent years, it has been scientifically proven that free radicals and oxidative stress cause the development of various diseases in the body. Since artificial antioxidants can have a negative effect on health, bioactive substances obtained from natural sources - medicinal plants - are gaining importance. Therefore, determining the antioxidant activity of medicinal plants expands the possibilities of their use in the pharmaceutical, cosmetology and food industries.